Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1002/cmdc.201300305
|View full text |Cite
|
Sign up to set email alerts
|

Target Hopping as a Useful Tool for the Identification of Novel EphA2 Protein–Protein Antagonists

Abstract: Lithocholic acid (LCA), a physiological ligand for the nuclear receptor FXR and the G-protein-coupled receptor TGR5, has been recently described as an antagonist of the EphA2 receptor, a key member of the ephrin signalling system involved in tumour growth. Given the ability of LCA to recognize FXR, TGR5, and EphA2 receptors, we hypothesized that the structural requirements for a small molecule to bind each of these receptors might be similar. We therefore selected a set of commercially available FXR or TGR5 li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
(60 reference statements)
1
22
0
Order By: Relevance
“…On the other hand, UniPR129 is the most potent low MW compound currently available capable of inhibiting not only phosphorylation of endogenous EphA2 in cells, but also cell retraction and endothelial capillary‐like tube formation. Furthermore, UniPR129 is active as an EphA2 antagonist in cellular functional assays at concentrations as low as 3–6 μM, whereas cholanic acid is active at 12–25 μM concentrations (Tognolini et al ., ), disalicylic derivatives at 25–50 μM (Noberini et al ., ), the agonist doxazosin at 25–50 μM (Petty et al ., ), green tea‐derived epicathechin gallates at 25–100 μM (Noberini et al ., ), dimethylpyrrolyl derivatives at 100–200 μM (Noberini et al ., ) and the recently discovered stilbene carboxylic acid derivatives (Tognolini et al ., ). Lastly, the potency of UniPR129 is comparable to that of the B11 antibody, which targets ephrin‐B2 and has a threshold concentration in functional anti‐angiogenesis assays of about 3 μM (Abéngozar et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, UniPR129 is the most potent low MW compound currently available capable of inhibiting not only phosphorylation of endogenous EphA2 in cells, but also cell retraction and endothelial capillary‐like tube formation. Furthermore, UniPR129 is active as an EphA2 antagonist in cellular functional assays at concentrations as low as 3–6 μM, whereas cholanic acid is active at 12–25 μM concentrations (Tognolini et al ., ), disalicylic derivatives at 25–50 μM (Noberini et al ., ), the agonist doxazosin at 25–50 μM (Petty et al ., ), green tea‐derived epicathechin gallates at 25–100 μM (Noberini et al ., ), dimethylpyrrolyl derivatives at 100–200 μM (Noberini et al ., ) and the recently discovered stilbene carboxylic acid derivatives (Tognolini et al ., ). Lastly, the potency of UniPR129 is comparable to that of the B11 antibody, which targets ephrin‐B2 and has a threshold concentration in functional anti‐angiogenesis assays of about 3 μM (Abéngozar et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A significant reduction of metastases was observed in the group treated with both ephrinA1-Fc or 135H12 treatments. Therapeutic targeting of the EphA2-LBD has been pursued in recent years by several different approaches [ 6 , 21 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ] and most studies envisioned the use of agonistic agents as vehicles for targeted delivery of chemotherapy [ 17 , 18 , 19 , 20 , 21 , 24 ]. Indeed, we had recently demonstrated that an earlier generation EphA2-targeting-peptide, when conjugated with paclitaxel, was remarkably effective in inhibiting lung metastases in a syngeneic mouse model of breast cancer [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides LCA and its analogues, small molecules that interfere with the EphA2-ephrin A1 system comprise the following: (i) the FXR agonist GW4064 [ 65 ], a stilbene carboxylic acid, dose-dependently disrupts the EphA2-ephrin A1 complex (IC50 = 23 μM), inhibits EphA2 phosphorylation (IC50 = 31 μM) and blocks EphA2 activation in prostate cancer cells; (ii) the disalicylic acid-furanyl derivative 76D10 (5,5′-(5,5′-((1E,4E)-3-oxopenta-1,4-diene-1,5-diyl)bis(furan-5,2-diyl))bis(2-hydroxybenzoic acid) inhibits ephrin interaction with EphA2, reducing EphA2 phosphorylation stimulated by ephrin-A1 Fc and inhibiting EphA2-mediated cell retraction in prostate cancer cells [ 66 ].…”
Section: Targeting Epha2 In Cancermentioning
confidence: 99%